2022
DOI: 10.3390/plants11030398
|View full text |Cite
|
Sign up to set email alerts
|

A New Essential Oil from the Leaves of the Endemic Andean Species Gynoxys miniphylla Cuatrec. (Asteraceae): Chemical and Enantioselective Analyses

Abstract: A previously uninvestigated essential oil (EO) was distilled from Gynoxys miniphylla Cuatrec. (Asteraceae) and submitted to chemical and enantioselective analyses. The qualitative and quantitative analyses were conducted by GC-MS and GC-FID, over two orthogonal columns (5%-phenyl-methylpolysiloxane and polyethylene glycol stationary phases). Major constituents (≥2%) were, on both columns, respectively, as follows: α-phellandrene (16.1–17.2%), α-pinene (14.0–15.0%), germacrene D (13.3–14.8%), trans-myrtanol ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…For these reasons, the discussion of the present volatile fraction focuses on its terpene components. With this respect, the chemical composition of this EO is coherent with the one discussed, in a previous paper, for the entire genus Gynoxys and especially for the species G. miniphylla [ 18 ]. In fact, we can find many common major components, which can be better visualized normalizing each amount to the only terpene fraction, in order to neglect the contribution of the heavy components.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For these reasons, the discussion of the present volatile fraction focuses on its terpene components. With this respect, the chemical composition of this EO is coherent with the one discussed, in a previous paper, for the entire genus Gynoxys and especially for the species G. miniphylla [ 18 ]. In fact, we can find many common major components, which can be better visualized normalizing each amount to the only terpene fraction, in order to neglect the contribution of the heavy components.…”
Section: Discussionsupporting
confidence: 84%
“…As discussed in a previous paper, we selected the poorly studied genus Gynoxys as a promising taxon for a systematic investigation. Despite the leaves not usually being very fragrant, a preliminary unpublished analysis indicated that the EOs from this genus are dominated by the sesquiterpene fraction [ 18 ]. For what concerns Gynoxys rugulosa Muschl., this species is poorly described also from the botanical point of view.…”
Section: Introductionmentioning
confidence: 99%
“…(Lamiaceae), which produces appreciable amounts of carnosol, a compound with potent anti-BuChE activity [81]; Gynoxys miniphylla Cuatrec. (Asteraceae), whose EO exhibits promising cholinergic, antiviral, and analgesic effects [82], and Clinopodium tomentosum (Kunth) Govaerts (Lamiaceae), whose leaf extract influences in vitro cell proliferation and angiogenesis on primary cultures of porcine aortic endothelial cells [83].…”
Section: Discussionmentioning
confidence: 99%
“…AH, belonging to the Allium family, has a strong sulfur flavor; hence, essential oils of nutmeg seed, which contains a higher essential oil content than cinnamon bark, were added to reduce its flavor (Figure 5A). Our results showed that the essential oil of nutmeg seed had 15 types of flavor components, with alpha-pinene, sabinene and beta-pinene as major components (Figure 5B), which are also found to exhibit antiallergic effects when extracted from Lepechinia betonicifolia and Gynoxys miniphylla [35][36][37]. Major components were detected in essential oils from Flos magnoliae with inhibitory effects on allergic rhinitis [38,39].…”
Section: Discussionmentioning
confidence: 99%